Identification of cognitive, affective, and practical aspects of Physical Education teachers regarding injury management - Fathya Nabila Putri Cahyani; Indra Himawan Susanto; Yetty Septiani Mustar; Anada Perwira Bakti (Sriwijaya Journal of Sport, 2025)
Research Problems: The handling of sports injuries by physical education teachers in the field is still not optimal, with survey results showing low knowledge and practice of the PRICES method. Improper handling has the potential to worsen the condition of injuries, while information and training related to the PRICES method are not yet evenly distributed among teachers. Research Objectives: This study aims to determine the level of knowledge, attitudes, and practices of physical education teachers in providing first aid for sports injuries using the PRICES method in Pasuruan Regency. Methods: The study used a quantitative descriptive approach with a questionnaire consisting of 54 items distributed via Google Form. The population consisted of 35 physical education teachers from elementary, junior high, and high schools in Prigen Subdistrict using a total sampling technique. The data were analysed descriptively using percentages. Results: Many of the teachers (74%) were categorised as very poor, poor, and adequate in their knowledge, attitudes, and practices related to PRICES, while only 26% were categorised as good and very good. This indicates a lack of understanding and implementation of effective injury management protocols in schools. Conclusion: There is a need for comprehensive capacity building for physical education teachers, particularly in the affective and psychomotor aspects, as well as adequate training and facilities to improve preparedness for handling sports injuries in schools.